A LITERATUR REVIEW: SUMBANGSIH PERAN MOHAMMAD NATSIR UNTUK INDONESIA: Mohammad Natsir - Mas Rukhin Lubabul huda (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This research discusses the contribution of Mohammad Natsir's role for Indonesia, which aims to commemorate Mohammad Natsir's services for Indonesia and introduce history to the wider community. The aim of this research is to identify the Muslim figure Mohmmad Natsir as a figure who played an important role in the progress of Islam in Indonesia. In this study, using a library study with a literature review approach by collecting from several sources of articles from the last 10 years in Google Scholar with the keyword